Recorded gestational violence and neonatal outcomes in a cohort of deliveries requiring neonatal hospitalization: a 15-year hospital-based perinatal registry study - Santiago Vasco-Morales; Mercy Rosero-Quintana; Alexandra Amaguaya-Guala; Emily Tamayo-Saenz; Paola Toapanta-Pinta (Frontiers in Global Women's Health, 2026)
Background Gestational violence is incompletely captured in routine perinatal registries, limiting prevalence estimation and etiologic interpretation. We evaluated associations between registry-recorded gestational violence, maternal characteristics, and neonatal outcomes in a selected hospital-based population. Methods This cross-sectional study included 26,519 delivery records from the Perinatal Information System at a tertiary referral hospital in Quito, Ecuador, from January 2009 to June 2024. Eligibility was restricted to deliveries whose newborns required neonatal hospitalization. Associations were estimated using maximum-likelihood, Firth-penalized, and Bayesian logistic regression. Neonatal analyses examined 12 prespecified outcome–trimester combinations, analyzed as exploratory. Sensitivity analyses addressed behavioral co-exposures, exposure misclassification, informative missingness, calendar time, prior specification, unmeasured confounding, and third-trimester ascertainment opportunity. Results Gestational violence was recorded in 1.19% of deliveries. The strongest maternal associations were observed for illicit drug use [Bayesian odds ratio [OR], 6.44; 95% credible interval [CrI], 3.78–10.74], passive smoking (OR, 3.56; 95% CrI, 2.62–4.79), and alcohol use (OR, 3.18; 95% CrI, 2.19–4.54). Third-trimester recorded violence showed the most consistent association with preterm birth (OR, 1.325; 95% CrI, 0.956–1.822; E-value, 1.57), corresponding to a risk difference of 6.5 percentage points (95% confidence interval, −0.8–14.2). The estimate weakened when restricted to births ≥34 weeks and when adjusted for calendar-related registry completeness, but increased modestly with adjustment for behavioral markers. These findings should not be interpreted as establishing causal associations. Conclusions Routine perinatal registry data may be useful for hypothesis generation and for guiding clinical and epidemiologic research until stronger evidence from prospective studies using validated violence-assessment instruments becomes available.